Apocalypse as holy war: divine politics and polemics in the Letters of Paul - Wasserman, Emma (The Anchor Yale Bible Reference Library, 2018)
Cover -- Half Title -- Title -- Dedication -- Contents -- Acknowledgments -- List of Abbreviations -- Introduction: The Politics of Heaven -- 1. Creation, Battle, and Cosmic Intrigue -- 2. Assemblies, Councils, and Ranks of Divinity -- 3. Conflict, Competition, and Paul's "Principalities and Powers" Reconsidered -- 4. Idols and Other Gods in 1 Corinthians, Galatians, and Romans -- 5. Victimization, Alienation, and Privilege Among the Christ-Elect -- Conclusion: Apocalypse as Holy War -- Notes -- Bibliography -- General Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- X -- Y -- Z -- Index of Ancient Sources